The adenoma miss rate of blue-laser imaging vs. white-light imaging during colonoscopy: a randomized tandem trial - Shimoda, Ryo; Sakata, Yasuhisa; Fujise, Takehiro; Yamanouchi, Kohei; Tsuruoka, Nanae; Hara, Megumi; Nakayama, Atsushi; Yamaguchi, Daisuke; Akutagawa, Takashi; Fujimoto, Kazuma; Iwakiri, Ryuichi (Endoscopy, 2017)
Background and study aims The aim of the present study was to determine whether blue-laser imaging (BLI) reduced the miss rate of colon adenomatous lesions compared with conventional white-light imaging (WLI).Patients and methods This was a prospective randomized study of patients undergoing screening and/or surveillance colonoscopy at Saga Medical School, Japan. A total of 127 patients were randomized to tandem colonoscopy with BLI followed by WLI (BLI-WLI group) or WLI followed by WLI (WLI-WLI group). The main outcome measure was the adenoma miss rate.Results The proportion of patients with adenomatous lesions was 62.5 % (40 /64) in the BLI-WLI group and 63.5 % (40 /63) in the WLI-WLI group. The total number of adenomatous lesions detected in the first inspection of the BLI-WLI and WLI-WLI groups was 179 and 108, respectively, compared with 182 and 120 in the second inspection, respectively. The miss rate in the BLI-WLI group was (1.6 %), which was significantly less than that in the WLI-WLI group (10.0 %, P = 0.001).Conclusions Colonoscopy using BLI resulted in a lower colon adenoma miss rate than WLI.Trial registration UMIN 000015677.